ASSET APPRECIATION Its Economic and Accounting Significance. - Krebs, William S. (The Accounting Review, 1930)
Accounting at the outset was concerned largely with the financial relations existing between a concern and its customers and creditors. Very soon, however, this narrow aspect of accounting was modified so that the accounts would record all assets and liabilities and make possible the construction of the balance sheet directly from the ledger. Then followed additional changes which permitted the presentation of a profit and loss statement. In all instances, however, the accountant was concerned largely with recording the historical changes in the financial and operating aspects of the business. Although some thought was given to the uses to which these statements might be put the primary consideration involved showing the chronological events from the point of view of what had happened and whether any irregularities were disclosed. Later when it became evident that accounting possessed an important relationship to management, the accounts and particularly the statements, were modified. Accrued and deferred items became recognized, with consequent changes in the balances of the income and expense accounts, so that the latter displayed incomes earned and expenses incurred by periods.